The ages of globalization. Geography, technology, and institutions - Medeiros, E. (European Planning Studies, 2020)
When, in 2015, Jeffrey D. Sachs, published The Age of Sustainable Development, it seemed to me to be the culmination of a life's work of a renowned academic in providing a crucial contribution to build a sustainable development rationale. However, the publication of his latest book proves that, far from signalling the end of a brilliant academic career, this is yet another accomplishment in offering a comprehensive review of current global development challenges and a range of potential solutions to some of them. Sachs starts by defining globalization as ‘the interlinkages of diverse societies across large geographical areas. These interlinkages are technological, economic, institutional, cultural, and geopolitical’ (p. 23). While there has been considerable research attention dedicated to a better understanding of this concept, Sachs focuses his on the ‘complexities of globalization, including the powerful capacity of globalization to improve the human condition while bringing undoubted threats as well’ (p. 16). In essence, rather than providing a normative and descriptive treatment of the subject, Sachs uses the knowledge acquired during a lifetime to provide a useful global analysis and set of potential solutions. Ultimately, its main novelty is the author's classification proposal for seven distinct ages of globalization, even though he recognizes that humanity has always been globalized.